Hukum Adat dalam Penyelenggaraan Pemerintahan Desa Adat di Kabupaten Siak Provinsi Riau dan Provinsi Bali - Muhammad April; Muammar Alkadafi; Muh. Said (Jurnal Hukum IUS QUIA IUSTUM, 2023)
The village as a customary law community unit has its original composition, which is the right of origin that is recognized in the framework of the 1945 Constitution. The implications of the implementation of Law Number 6 of 2014 on Villages revived the spirit of the Regional Government of Siak Regency and Bali Province to carry out the arrangement of a model of governance of traditional villages that are appropriate with the origins and customs that once prevailed in the region. This study analyzes; first, the impact of the enactment of the village law on the governance of traditional villages in Siak District, Riau Province and Bali Province. Second, aspects that become similarities and differences in the administration of traditional village governance between Siak Regency, Riau Province and Bali Province. This study uses empirical normative research method. The results of the study concluded that first, the administration of traditional village governance in Siak Regency, Riau Province was not carried out, while the existence of traditional villages in Bali Province was getting stronger through government policies that gave special status and authority to traditional villages to organize traditional village governance in accordance with their origins and customs that exist in society. Second, the institutional administration of traditional villages in Siak Regency is no longer based on the original structure and no longer carries out activities according to customs and traditions in the context of Malay culture, while in Bali institutional governance of traditional villages and community activities are still based on the values of their ancestral culture, namely the philosophy of tri hita karana.Keywords: Traditional Village; Customary Law; Public Policy; Government AbstrakDesa sebagai kesatuan masyarakat hukum adat mempunyai susunan asli, hak asal usul yang diakui dalam kerangka UUD 1945. Implikasi pemberlakuan Undang-Undang Nomor 6 Tahun 2014 tentang Desa memunculkan kembali spirit Pemerintah Daerah Kabupaten Siak dan Provinsi Bali untuk melakukan penataan model pemerintahan desa adat yang sesuai dengan asal usul dan adat istiadat yang pernah berlaku di wilayah tersebut. Penelitian ini menganalisis; pertama, dampak pemberlakuan undang-undang desa terhadap penyelenggaraan pemerintahan desa adat di Kabupaten Siak Provinsi Riau dan Provinsi Bali. Kedua, aspek-aspek yang menjadi persamaan dan perbedaan penyelenggaraan pemerintahan desa adat antara Kabupaten Siak Provinsi Riau dan Provinsi Bali. Penelitian ini menggunakan metode penelitian normatif empiris. Hasil penelitian menyimpulkan bahwa, pertama, penyelenggaraan pemerintahan desa adat di Kabupaten Siak Provinsi Riau tidak terlaksana, sedangkan desa adat di Provinsi Bali eksistensinya semakin kuat melalui kebijakan pemerintah yang memberikan status dan kewenangan khusus kepada desa adat untuk menyelenggarakan pemerintahan desa adat sesuai dengan asal usul dan adat istiadat yang ada di masyarakat. Kedua, Pemerintahan desa adat di Kabupaten Siak kelembagaannya tidak lagi berdasarkan susunan aslinya dan tidak lagi beraktifitas secara adat-istiadat dalam konteks kebudayaan melayu, sedangkan di Bali pemerintahan desa adat secara kelembagaan dan aktivitas masyarakatnya masih berdasarkan nilai-nilai kebudayaan leluhurnya yaitu falsafah tri hita karana. Kata-kata Kunci: Desa adat; Hukum Adat; Kebijakan Publik; Pemerintahan